Analisis Pelatihan Penggunaan Media Pembelajaran CD Interaktif Berbasis Multimedia Dan Modul IPA SD Kelas III di Kecamatan Koto Tangah Kota Padang - Nelda Azhar; Kasman Rukun; Asrul Huda (Jurnal Pendidikan Teknologi Kejuruan, 2019)
Teachers and the world of education are generally expected to be able to create quality human resources both scientifically and positively. For this reason, in the learning process, the methods, strategies or learning activities carried out by the teacher should be something that is truly appropriate and meaningful, to obtain maximum results according to the stage of development of the child, then the strategies that the teacher uses in conveying something, both in the form of planting attitudes, mentality, behavior, personality and intelligence must be on target, seven proportional intelligence. In our lives we cannot deny that the ones who determine the attitudes, mentality, behavior, personality and intelligence of children are education, experience and exercises given and experienced by students since they were small. The results of the preliminary survey showed that several schools belonging to the Teacher Working Group (KKG) of Cluster V for science learning in SD III had not shown optimal learning. The results of the initial survey showed that the teacher working group (KKG) incorporated in the IV cluster V region of Koto Tangah Subdistrict, amounting to 11 schools, often experienced problems in the school learning process that had not been carried out optimally due to lack of learning media and science learning aids. The lecture activities carried out by the teacher were not wrong at all, but when lecturing, the teacher's interaction with students was not very running, the teacher only tended to lecture and did not pay attention to the situation and condition of students in the class. The lecture method also cannot be separated from the learning process. The lecture method will make students get maximum learning outcomes if packaged better and interestingly.